Fabrication of a super-hydrophobic and high-roughness terrace-effect membrane for enhanced flux and fouling resistance - Talukder, Md Eman; Talukder, Md. Romon; Pervez, Md. Nahid; Kujawski, Wojciech; Figoli, Alberto; Naddeo, Vincenzo (Desalination and water treatment, 2025)
The current study reported a novel terrace effect on the membrane surface, which is a straightforward and practical approach to enhancing membrane performance characterized by high roughness, thermal stability, and extended durability. We prepared pure PVDF and terraced PVDF membrane using several membrane fabrication methods, Delayed non-solvent Induced Phase Separation (D-NIPS) and Thermally Induced Phase Separation (TIPS), along with Vapor-Induced Phase Separation (VIPS) processes with solvent/water mix vapor flow. These methods were complemented by adjusting the coagulation bath composition and temperature, followed by surface fluorination and surfactant sodium dodecyl sulfate (SDS) to reduce the membrane's surface energy and the surface tension of the feed saltwater. The resulting super-hydrophobic pure PVDF, terraced effect porous PVDF membranes, terraced effect PVDF-FS membranes with high roughness 72 ± 4.3 nm, 360 ± 20 nm, 401 ± 24 nm, and a water contact angle (WCA) of 109 ± 1.1°, 138 ± 1.5°, 147 ± 2.9°. Our results demonstrated that membranes with terrace effect super-hydrophobic surfaces achieved a high flux of 9.6 Lm−2h−1 for pure PVDF, and 25.2 Lm−2h−1 for terrace effect porous PVDF, offering a significant advantage for MD treatment. [Display omitted] •Designed a new surface structure on the membrane surface.•Terrace-effect porous membrane with high roughness and superhydrophobicity properties.•New structure improved the flux and fouling resistance of membrane.•Terrace-effect MD membrane retard membrane scaling.